(untitled) (Islamic Sciences Journal, 2024)
The current study addressed: 1-Deducing the jurisprudential rule in the chapter on prayer from the book Al-Mustasfa by Abu Al-Barakat 2. Relying on induction and using quite a few important ancient and modern sources that the research needs. 3- Explaining the rule, explaining its general meaning, and defining its vocabulary linguistically and terminologically, using books on language and principles. 4- Mentioning the evidence for rooting the jurisprudential rule from the Gloriuos Qur’an or Sunnah, if any. 5-Applications of the jurisprudential rule were mentioned in this book, and the first application was from Al-Nasafi’s book Al-Mustasfa. 6-Since the jurisprudential rule is derived from the book of the Hanafi school of thought, I, in turn, limited my study of it from the perspective of the Hanafi jurists, may Allah the Almighty have mercy on them. Among the findings: 1-The jurisprudential rules in the book Al-Mustasfa by Al-Nasafi are mostly agreed upon among Hanafi jurists, may Allah the Almighty have mercy on them. 2-The jurisprudential rules in the book Al-Mustasfa are derived from the texts of the Qur’an and the Sunnah of the Prophet. 3- Jurisprudential rules are based on removing embarrassment from people.